The Incidence of the Application of Participative Techniques in the Development of Fluency in the Review Two of CENDIA C.A. - Cobo Cueva, José Antonio (2008)
The present research work was made in order to understand the need to improve the teaching and learning process, especially in languages in this case the English Language. CENDIA was the institution who let the research go over the investigation with its 2 Final levels which are called "Review Two". Once the real concepts of fluency and participative techniques were clarified and clearly stated, the research took place in the levels above mentioned at CENDIA, a prestigious Institution of Quito with more than 30 years of experience in the field The basic points treated in the research work were how influent and important participative techniques are in the improvement of English skills and in the development of fluency. In order to carry this out, it was necessary to develop a cuasi - experimental study that consisted of the analysis of two groups of the same level of English knowledge. First of all, the groups were formed: one experimental group in which the participative techniques were applied and the other was the control group whose teacher never applied the mentioned techniques during the same period of time, at the same time and schedule so the experiment does not have external factors influencing in the participants. After the time in which the experiment took place results came out confirming the stated hypothesis. The participative techniques certainly improve learning process, fluency and make the class more interesting and students more satisfied.